Investigating the role of environmental concern and the unified theory of acceptance and use of technology on working from home technologies adoption during COVID-19 - Razif, Mohammad; Miraja, Bobby Ardiansyah; Persada, Satria Fadil; Nadlifatin, Reny; Belgiawan, Prawira Fajarindra; Redi, Anak Agung Ngurah Perwira; Lin, Shu-Chiang (Entrepreneurship and Sustainability Issues, 2020)
Working From Home (WFH) technologies has been used and discussed for a long time. The many positive benefits of WFH technologies, including its potential to create a more sustainable work activity, attracted many studies to gain a better understanding of this subject. This study is interested to understand the different factors, including environmental, influencing WFH technologies acceptance in this current shifting situation stimulated by the Covid-19 pandemic. An extended Unified Theory of Acceptance and Use of Technology (UTAUT) model, employing Environmental Concern, was used. The model was assessed by using the structural equation model. The total of 172 respondents participated in this research. The total of 5 hypotheses was tested. The present study’s model is able to predict 57.4% of WFH Technology acceptance. Finally, discussion and recommendations to businesses that are currently taking WFH measures during the Covid-19 pandemic were presented.